2018
DOI: 10.18203/2349-3933.ijam20181082
|View full text |Cite
|
Sign up to set email alerts
|

Patients characteristics associated with better glycemic response to teneligliptin and metformin therapy in type 2 diabetes: a retrospective study

Abstract: Background: Teneligliptin was recently approved for type 2 diabetes (T2D) management in India and is used as monotherapy or in combination with different antidiabetic drugs. The aim of this study was to identify patients’ characteristics associated with better glycemic response to teneligliptin and metformin.Methods: A retrospective analysis of data was performed in patients of T2D with HbA1c above 7% who were treated with teneligliptin 20 mg/d as add on to metformin (500-100 mg/d) and whose follow-up data at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…In present study, group-A patients who were treated with metformin and glimepiride had shown a significant decline in mean FPG, PPG and HbA1c levels, similar results were found in another study 10 . There was significant reduction in mean FPG, PPG and HbA1c observed in group B patients who received metformin and teneligliptin (p<0.05), which is in line with previous studies 11,12 .…”
Section: Discussionsupporting
confidence: 92%
“…In present study, group-A patients who were treated with metformin and glimepiride had shown a significant decline in mean FPG, PPG and HbA1c levels, similar results were found in another study 10 . There was significant reduction in mean FPG, PPG and HbA1c observed in group B patients who received metformin and teneligliptin (p<0.05), which is in line with previous studies 11,12 .…”
Section: Discussionsupporting
confidence: 92%
“…Data from real-world, retrospective study (Treat-India) suggests that Teneligliptin significantly (p < 0.001) improves glycemic control in T2DM patients, when prescribed either as monotherapy or in combination with Metformin compared with SU combination therapy. [ 62 63 ]…”
Section: Purpose Of the Expert Opinionmentioning
confidence: 99%